Continuous within‐plant variation as a source of intraspecific functional diversity: Patterns, magnitude, and genetic correlates of leaf variability in Helleborus foetidus (Ranunculaceae)1. Issue 2 (1st February 2015) - Herrera, Carlos M.; Medrano, Mónica; Bazaga, Pilar
Abstract : Premise of the study: Continuous within‐plant variation in quantitative traits of reiterated, homologous structures is a component of intraspecific variation, but its contribution to functional diversity remains largely unexplored. For the perennial Helleborus foetidus, we measured functional leaf traits to quantify the contribution of within‐plant variation to intraspecific functional variance and evaluate whether within‐plant variability itself deserves separate consideration. Methods: Within‐individual variation in eight leaf traits was quantified for 138 plants sampled from 10 widely spaced locations in the Sierra de Cazorla, southeastern Spain. An amplified fragment length polymorphism (AFLP) technique was used to look for associations between within‐plant variability and specific AFLP markers. Key results: Leaflets from basal positions in ramets were longer, heavier, had greater surface area and larger stomata, and lower specific area, stomatal index, and stomatal density than those from distal positions. Continuous variation between leaves from the same ramet was the main source of population‐wide variance for most traits. Within‐plant variability differed among populations. Individuals differed in within‐plant variability, which was largely independent of trait means and associated with genetic characteristics. Up to four AFLP markers were associated with the within‐plant variability level of a given leaf trait. Conclusions: Subindividual variability in continuous leaf traits was independent of plant means and related to genetic features. The within‐individual component generally exceeded the between‐individual component of intraspecific variance. Within‐plant variation may broaden the ecological breadth and enhance stability and persistence of plant populations and communities and may provide novel insights when incorporated in trait‐based community ecology models.